SOSIALISASI PERAN PKK DAN KADER DESA DALAM PENANGANAN STUNTING DI DESA COMPANG NDEJING, KECAMATAN BORONG, KABUPATEN MANGGARAI TIMUR - tulle, visto; Pegan, Ricardo Arkian; Bere, Mikael Aldi; Lawalu, Stephanie Perdana Ayu (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2025)
This article discusses a community service program in the form of a socialization activity on the role of the Family Welfare Movement (PKK) and Village Cadres in addressing stunting issues for PKK members, village cadres, and the community in Purang Mese, Compang Ndejing Village, Borong District, East Manggarai Regency. This activity is motivated by the importance of PKK and village cadres understanding their main duties and functions in tackling stunting. This program aims to raise awareness among PKK members and village cadres regarding their roles and responsibilities. The methods used include observation, simulation, evaluation, and feedback. The activity was held on April 11, 2025, involving PKK administrators, village cadres, and the local community. The materials provided covered the definition of stunting, the duties and functions of PKK and village cadres, core PKK and cadre programs, the role of PKK and village cadres in addressing stunting issues, and joint strategies.